Improved Transplant‐Free Survival in Patients With Systemic Sclerosis–Associated Pulmonary Hypertension and Interstitial Lung Disease. Issue 7 (July 2014) - Volkmann, Elizabeth R.; Saggar, Rajeev; Khanna, Dinesh; Torres, Bryant; Flora, Arjan; Yoder, Lynne; Clements, Philip J.; Elashoff, Robert M.; Ross, David J.; Agrawal, Harsh; Borazan, Nabeel; Furst, Daniel E.; et al.
<x xml:space="preserve">Abstract</x> Objective Survival in patients with systemic sclerosis (SSc)–associated pulmonary hypertension (PH) and interstitial lung disease (ILD) is poor. Evidence supporting the efficacy of aggressive pulmonary arterial hypertension (PAH)–targeted therapy in this population is limited. The aim of this study was to investigate transplant‐free survival in patients with isolated SSc‐related PAH or SSc‐related PH‐ILD who were treated with aggressive PAH‐targeted therapy. Methods SSc patients with right‐sided heart catheterization (RHC)–diagnosed precapillary PH (mean pulmonary artery pressure ≥25 mm Hg, pulmonary capillary wedge pressure ≤15 mm Hg, and pulmonary vascular resistance ≥240 dynes × second/cm5) were included. Patients were classified as having ILD based on review of high‐resolution computed tomography (CT) chest imaging and spirometry. The Kaplan‐Meier method was applied and Cox proportional hazards models were constructed to analyze survival and identify predictive variables. Results Of 99 patients with SSc‐related precapillary PH, 28% had SSc‐related PAH and 72% had SSc‐related PH‐ILD. The 1‐ and 2‐year survival estimates were, respectively, 72% and 59% in the SSc‐related PH‐ILD group versus 82% and 66% in the SSc‐related PAH group (P = 0.5). Within 6 months of the diagnostic RHC, 24% of all patients were started on prostanoid therapy; an additional 24% were started on prostanoid therapy after 6 months. In the multivariate model, male sex (hazard ratio [HR] 0.7, P = 0.01) and prostanoid therapy initiation within 6 months of the RHC (HR 1.4, P = 0.01) were the only factors significantly associated with transplant‐free survival, after accounting for the presence of ILD and severity of PH. Conclusion In this study, survival of patients with SSc‐related PH‐ILD was modestly improved relative to historical series. While these findings may not be generalizable, improved survival may be due partly to aggressive PAH‐targeted therapy.